Anti-p200 pemphigoid (anti-laminin-γ1 pemphigoid) demonstrating pathergy - Morgan McCarty, DO; Deltef Zillikens, MD; David Fivenson, MD (Wolters Kluwer, 2015)
Anti-p200 pemphigoid, also called anti-laminin-γ1 pemphigoid, is a recently defined entity. First reported in 1996, the incidence is relatively rare, with approximately 70 reports in the literature. Clinical presentation is heterogeneous, but the disease most commonly mimics bullous pemphigoid with urticarial papules, plaques, or tense bullae on the trunk or extremities. Described here is a case with additional features of pathergy that have not yet been reported in the literature.